NOW THE SOLUTION IS HERE – SOCIAL ASSISTANCE FOR ORPHANED CHILDREN: THE EXTENDED CHILD SUPPORT GRANT - Sibanda, Sipho; Ndamba, Felistus (Social Work, 2023)
The current crisis in foster care was precipitated by using the child protection system to meet the social assistance needs of orphaned children. The new parallel system in the form of an extended child support grant system would enable children in the care of relatives to access an appropriate grant without having to go through a time-consuming and resource-intensive statutory process. This article outlines the challenges in the South African foster care system, discusses the reasons for introducing the extended child support grant system and explains how it will be implemented. The paper seeks to contribute to the knowledge base on social work policy changes. The policy shift towards an extended child support grant could ensure that the majority of orphans have access to adequate social protection and free up the formal child protection system, enabling a quicker social work response to cases of child abuse, maltreatment and neglect.